Posttraumatic stress disorder symptoms after respiratory and cardiovascular emergencies predict risk of hospital readmission: A prospective cohort study. (10th February 2022) - Kovalsky, Danielle; Roberts, Michael B.; Freeze, Brian; Moss, Jeena; Jones, Christopher W.; Kilgannon, Hope; Edmondson, Donald E.; Trzeciak, Stephen; Fuller, Brian M.; Roberts, Brian W.
Abstract: Background: Twenty‐five percent of patients presenting to the emergency department (ED) for a respiratory or cardiovascular medical emergency develop clinically significant posttraumatic stress disorder (PTSD) symptoms. It is possible that development of PTSD symptoms in this cohort is associated with subsequent adverse physical health events. Our objective was to test whether clinically significant PTSD symptoms 30 days postdischarge are associated with increased risk for hospital readmission within 24 months after discharge among patients presenting to the ED for a respiratory or cardiovascular emergency. Methods: This was a prospective cohort study conducted between January 1, 2018, and December 31, 2020, at a U.S. academic medical center, including adult patients presenting with acute respiratory failure or cardiovascular instability requiring a potentially life‐sustaining intervention in the ED. PTSD symptoms 30 days postdischarge were measured using the PTSD Checklist for the Diagnostic and Statistical Manual of Mental Disorders‐5 . The primary outcome was all‐cause hospital readmission over the subsequent 24 months after hospital discharge from the index ED visit. Results: Of the 99 patients included, 73% (95% confidence interval [CI] = 63% to 81%) had a hospital readmission within 24 months. In a multivariable Cox proportional hazards model adjusting for potential confounders (e.g., age, severity of illness during index ED visit, preexisting comorbid conditions) presence of clinically significant PTSD symptoms at 30 days was independently associated with increased risk for all‐cause hospital readmission at 24 months (hazards ratio = 2.19, 95% CI = 1.30 to 3.69). These results remained statistically significant across multiple sensitivity analyses. Conclusions: Hospital readmission is common among survivors of acute respiratory failure and cardiovascular instability, and PTSD symptoms 30 days postdischarge are an independent predictor of hospital readmission. Survivors of medical emergencies may warrant follow‐up evaluation for PTSD symptoms, and future research is warranted to better understand the relationship between psychological trauma and hospital readmission.